PENGARUH SISTEM INFORMASI MANAJEMEN BERBASIS KOMPUTER TERHADAP KINERJA PEGAWAI KANTOR KELURAHAN TAMBUSAI TENGAH KABUPATEN ROKAN HULU - AH, Saprizal (Jurnal Mahasiswa Prodi Manajemen Fakultas Ekonomi, 2016)
This study aims to determine whether or not the influence of Computer-Based Information Management System Employee Performance Against Middle Village Office Tambusai Rokan Hulu. The sample in this study were all employees of the office Lurah Middle Tambusai Tambusai District of Rokan Hulu using the census as many as 30 (thirty) employees. The results of this study indicate that there is no significant effect between computer-based management information system to employee performance Tambusai village office Central (Score t <t table = -0.649 <2.04227), the initial hypothesis which states that there is significant influence between systems computer-based management information on the performance of employees at the village office Central Tambusai rejected and not truth. The conclusion was not a significant difference between computer-based management information system to employee performance District Office Central Tambusai Rokan Hulu